2013
DOI: 10.7589/2012-11-272
|View full text |Cite
|
Sign up to set email alerts
|

Severe Dental Fluorosis in Juvenile Deer Linked to a Recent Volcanic Eruption in Patagonia

Abstract: ABSTRACT:The Puyehue-Cordon Caulle volcanic eruption deposited large amounts of tephra (ashes) on about 36 million ha of Argentina in June of 2011. Tephra was considered chemically innoxious based on water leachates, surface water fluoride levels were determined to be safe, and livestock losses were attributable to inanition and excessive tooth wear. To evaluate effects on wild ungulates, we sampled wild red deer (Cervus elaphus) at 100 km from the volcano in SeptemberNovember 2012. We show that tephra caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…However, the main cause of livestock losses across the impacted area was due to starvation and gastrointestinal blockages. Some livestock were also affected by skin and eye irritations and infections (Robles 2012), possible chronic fluorosis (Flueck & Smith-Flueck 2013;Flueck 2014;Flueck 2013), and in Jacobacci there was a decline in wool quality and shearing rates (Aguirre 2012;Easdale et al 2014;Wilson et al 2012b).…”
Section: Agriculturementioning
confidence: 99%
“…However, the main cause of livestock losses across the impacted area was due to starvation and gastrointestinal blockages. Some livestock were also affected by skin and eye irritations and infections (Robles 2012), possible chronic fluorosis (Flueck & Smith-Flueck 2013;Flueck 2014;Flueck 2013), and in Jacobacci there was a decline in wool quality and shearing rates (Aguirre 2012;Easdale et al 2014;Wilson et al 2012b).…”
Section: Agriculturementioning
confidence: 99%
“…The low fluoride levels in fetal deer bones reported here, therefore, also indicate a placental barrier, particularly considering that concentrations in mothers were 109-fold higher. As expected, calves showed unaffected mandibular molars M1, which mineralize in utero and are established in 4-month-old calves (Flueck and Smith-Flueck 2013). Kay et al (1976) also found that skeletal fluoride levels in wild ungulates at birth were near zero.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, antlers shed in 2012 in one area and from males subjected to fluoride exposure averaged 657 ppm (Flueck and Smith-Flueck 2013). …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1a). Furthermore, fluoride concentrations in bone approached 5180 ppm, whereas the average level increased more than 3900 % after exposure to tephra for the first 15.5 months (Flueck and Smith-Flueck, 2013a). Furthermore, fluoride concentrations increased substantially in four age classes, at a rate of about 1000 ppm of F yr −1 on average.…”
Section: Introductionmentioning
confidence: 93%